Letter to F. J. Smrcina from Willie Houseal, September 6, 1983 - Houseal, Willie H. (Valdosta State University Archives and Special Collections, 1983)
The letter, dated September 6, 1983, is addressed to Mr. F. J. Smrcina for Willie Houseal as the Executive Director of the Winnerville Coalition Consultants. The topics of the letter include, utilization of Lomax Facilities for Voter Education Seminars and voter apathy.
1 electronic document, PDF, 1 scanned image
Keywords: Valdosta (Ga.); Lowndes County (Ga.); Voting; Correspondence